The Relationship Between Students’ Attitudes Towards Literature and Their Ability To Read Short Stories With Students’ Narrative Writing Skills RK Bintang Senior High School In East Pematangsiantar - Suryanto Marpaung, Michael; Sutikno (PT Inovasi Pratama Internasional, 2025)
The problem in this research is the relationship between attitudes towards literature and the ability to read short stories together with the narrative writing skills of class X SMA Swasta RK Bintang Timur Pematangsiantar students. The aim of this research is to describe the relationship between attitudes towards literature and the ability to read short stories, together with the narrative writing skills of class X SMA Swasta RK Bintang Timur Pematangsiantar students. The method used in this study was a descriptive method using correlation analysis techniques. The author used this method because the author wanted to find the relationship between the three variables in this research, namely attitudes towards literature (X1), ability to read short stories (X2), and narrative writing skills as variable Y. The population in this study was all classes, and the instruments used in data collection were tests and questionnaires. Tests were used to obtain data on short story reading abilities and narrative writing skills, and questionnaires were used to obtain data on students' attitudes towards the literature. The research results showed that